Best friends for Frances - Hoban, Russell; Hoban, Lillian (New York : HarperCollins, 1994)
When Albert and his buddies have a "no girls" baseball game, Frances and her sister organize a "Best Friends Outing--No Boys".
Elem. School Library Collection.
Library Journal.
School Library Journal.
3.5.
3.5
K-3
Keywords: Badgers -- Fiction; Brothers and sisters -- Fiction; Badgers -- Fiction; Siblings -- Fiction